Uncovering the true cost of hydrogen production routes using life cycle monetisation. (1st January 2021) - Al-Qahtani, Amjad; Parkinson, Brett; Hellgardt, Klaus; Shah, Nilay; Guillen-Gosalbez, Gonzalo
Highlights: Environmental externalities are crucial to sustainability assessments. Economical plus monetised LCA impacts provides an estimate of true cost of hydrogen. Ten hydrogen production technologies were assessed and compared on monetary basis. At present, steam methane reforming with CCS emerged as the most promising option. Abstract: Hydrogen has been identified as a potential energy vector to decarbonise the transport and chemical sectors and achieve global greenhouse gas reduction targets. Despite ongoing efforts, hydrogen technologies are often assessed focusing on their global warming potential while overlooking other impacts, or at most including additional metrics that are not easily interpretable. Herein, a wide range of alternative technologies have been assessed to determine the total cost of hydrogen production by coupling life-cycle assessments with an economic evaluation of the environmental externalities of production. By including monetised values of environmental impacts on human health, ecosystem quality, and resources on top of the levelised cost of hydrogen production, an estimation of the "real" total cost of hydrogen was obtained to transparently rank the alternative technologies. The study herein covers steam methane reforming (SMR), coal and biomass gasification, methane pyrolysis, and electrolysis from renewable and nuclear technologies. Monetised externalities are found to represent a significant percentage of the total cost, ultimately altering the standard ranking of technologies. SMR coupled with carbon capture and storage emerges as the cheapest option, followed by methane pyrolysis, and water electrolysis from wind and nuclear. The obtained results identify the "real" ranges for the cost of hydrogen compared to SMR (business as usual) by including environmental externalities, thereby helping to pinpoint critical barriers for emerging and competing technologies to SMR.